Pengaruh Kesiapan Sumber Daya Manusia Dan Teknologi Terhadap Adopsi Platform E-Commerce Shopee Serta Dampaknya Pada Kinerja Penjualan (Studi Pada Umkm Kuliner Di Kota Medan) - Alfaridho Sibarani; Tapi Rondang Ni Bulan; Annisha Suvero Suyar (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
This study aims to determine the effect of readiness of human resources, and technology has an effect on sales performance, to determine and analyze the effect of readiness of human resources and technology on the adoption of shopee e-commerce platform and its impact on sales performance. The population sampling method in this study amounted to 259,812, the population data registered in the UMKM data site belonging to the Cooperatives and Micro, Small and Medium Enterprises Office of North Sumatra province, and using the Slovin sampling technique, a sample of 100 Culinary SMEs was obtained. The technique used in collecting this data s using a survey through distributing questionnaires to culinary MSME users who run their business by e-commerce in the shopee application in the city of Medan. The results show that the readiness of human resources has no significant effect on sales performance, technology readiness does not significantly affect sales performance, the adoption of the shopee e-commerce platform mediates the effect of human resource readiness on sales performance, the adoption of the shopee e-commerce platform mediates the technological readiness to sales performance.